HBR Guide to Finance Basics for Managers - Havard business School (Havard Business Review Press, 2012)
The HBR Guide to Finance Basics for Managers will help you:Learn the language of finance. Compare your firm’s financials with rivals’. Shift your team’s focus from revenues to profits. Assess your vulnerability to industry downturns. Use financial data to defend budget requests. Invest smartly through cost/benefit analysis